PENGARUH PENGGUNAAN MODEL PROJECT-BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK - Nursaadah, Ulfah; Dinny Mardiana; Deti Ahmatika (Universitas Islam Nusantara, 2024)
The background of this research is the low problem solving abilities in learning mathematics, due to the less than optimal implementation of online learning in the last two years. One alternative learning that can be applied related to problem solving abilities is the project-based learning model (Project-Based Learning). The purpose of this study was to determine the effect of using the Project-Based Learning model on students' problem solving abilities in learning mathematics. The method used is a quasi-experimental method with the Nonequivalent Control Group Design. This research was conducted at MTs Wasilatul Huda. The population in this study were students of class VIII, with the sample being students of class VIII B as an experimental class using the application of the Project-Based Learning model, while the control class used the Discovery Learning model. The instruments used were tests of problem solving abilities. Based on the results of the analysis of the Mann-Withney test, Cohen's d, it is concluded that the use of the Project-Based Learning model affects problem solving abilities in the medium category.